Visual Prognosis in Craniosynostosis Patients: A 20-year Retrospective Cohort Study at a Tertiary Referral Center in Thailand - Thammanoon Surachatkumtonekul; Subongkoch Subhadhirasakul; Wasawat Sermsripong (Siriraj Medical Journal)
Objective: This study aims to evaluate the visual prognosis in craniosynostosis patients in order to identify ophthalmologic manifestations in craniosynostosis patients and strabismus surgery outcomes in these patients.